Model Penyajian Laporan Keuangan Berdasarkan Interpretasi Standar Akuntansi Keuangan Nomor 335 (ISAK 335) Pada Gereja Masehi Injili Di Timor - Sir, Jennie S.; Samadara, Selfesina; Tuati, Nonce F. (Politeknik Negeri Ambon, 2025)
This research aims to provide a practical solution to the problem of financial transparency and accountability of the Gereja Masehi Injili in Timor (GMIT) by developing a model for presenting church financial reports based on ISAK 335. This research employs qualitative methods, utilizing a case study approach. The research results indicate that GMIT prepares financial reports in a simple form, consisting of reports on cash receipts and cash disbursements, following the format established by the GMIT Synod. Furthermore, this research provides a model for presenting structured and detailed financial reports based on ISAK 335. The practical implications expected from this research are changes in the format and structure of presenting GMIT's financial reports, making them more comprehensive and accurate for users, particularly GMIT congregations. Keywords: church; financial statements; ISAK 335